2001
DOI: 10.1093/nar/29.1.55
|View full text |Cite
|
Sign up to set email alerts
|

A fully automatic evolutionary classification of protein folds: Dali Domain Dictionary version 3

Abstract: The Dali Domain Dictionary (http://www.ebi.ac.uk/dali/domain) is a numerical taxonomy of all known structures in the Protein Data Bank (PDB). The taxonomy is derived fully automatically from measurements of structural, functional and sequence similarities. Here, we report the extension of the classification to match the traditional four hierarchical levels corresponding to: (i) supersecondary structural motifs (attractors in fold space), (ii) the topology of globular domains (fold types), (iii) remote homologu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 11 publications
2
140
0
Order By: Relevance
“…We built a list of proteins to simulate the 30 most populated folds according to SCOP (30,31), CATH (32), Dali (33,34), and Dagget's databases (35) (see SI Data Set). When several good three-dimensional models exist in a class, we favor structures without bound ligands.…”
Section: Methodsmentioning
confidence: 99%
“…We built a list of proteins to simulate the 30 most populated folds according to SCOP (30,31), CATH (32), Dali (33,34), and Dagget's databases (35) (see SI Data Set). When several good three-dimensional models exist in a class, we favor structures without bound ligands.…”
Section: Methodsmentioning
confidence: 99%
“…The model was validated by calculating the solvation profile with SolvX software (38), which gave a satisfactory score of Ϫ17.5. The DALI algorithm (22) was used to align this model with the structure of the sensor domain of CitA (23).…”
Section: Methodsmentioning
confidence: 99%
“…One such special case are the ''interlogs'' (i.e., pairs of interacting proteins that interact identically in two species) (19). It has already been demonstrated that the information about the interacting partners can be used to predict the fold (7,(20)(21)(22) or function (14,(23)(24)(25)(26)(27)) of a protein without considering its sequence. The usefulness of these approaches should grow with time, given the increasing amount of data about protein-protein interactions (20,24,28) (4).…”
Section: Detecting Remotely Related Proteins By Their Interactions Anmentioning
confidence: 99%